Enhanced corrosion protection performance with MWCNT dispersed epoxy coating prepared under supercritical CO2 assistance. (21st June 2018) - Khanam, Zeba; Singh, Vir; Zaidi, Muhammad Ghulam Haider
Abstract : The corrosion protection performance of epoxy coatings could be enhanced by incorporation of nanofillers such as MWCNT. However, a homogeneous dispersion of MWCNT in epoxy polymer is still a teasing challenge. Herein, we report an environmentally benign single‐step supercritical CO2 processing method to improve the dispersion of MWCNT in epoxy matrix in order to achieve an effective anticorrosive coating. The executed approach provides a cluster‐free uniform distribution of MWCNT in epoxy matrix as characterized with UV‐visible spectroscopy, Fourier transforms infrared spectroscopy, X‐ray diffraction, and surface analysis. The anticorrosive characteristics of MWCNT/epoxy coating were studied in NaCl as well as in photodegraded dye medium through electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization measurements. We observed the remarkable corrosion of model metal substrate in photodegraded dye medium besides NaCl medium. In both mediums, the protection efficacy of MWCNT/epoxy coating was deduced from the stable impedance arcs in Nyquist plot and increased impedance modulus. The electrochemical impedance spectra were best fitted with equivalent circuits showing the higher values of pore resistance. Also, the MWCNT/epoxy coating exhibited a positive shift of corrosion potential and possessed a lower corrosion rate as compared with neat epoxy coating. More direct evidence of the excellent barrier properties for MWCNT/epoxy coating was visualized in SEM images. The obtained results implied that the superior dispersion of MWCNT into epoxy matrix significantly reduces the porosity of coating and inhibits the permeability of corrosive ions. We expect supercritical CO2 assisted dispersion method can offer an efficient, cost‐effective, and industrially viable route to develop high performance protective coatings for varied commercialized applications.